Trafikkulturell kompetens: en studie av åsikter om trafiken i Göteborg - Jonasson, Mikael (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Values, attitudes and behaviour have an impact on traffic safety. These values, attitudes and behaviour are often related to human interaction at a specific place, for instance a city. Together these values, attitudes and behaviours creates cultures in different rooms of traffic - different traffic cultures. In order to understand and change values and behaviour in traffic it is neccesary to know what a traffic culture is. The aim of this study is to see how the identity of traffic users, opinions and attitudes towards one another reflect their practical knowledge of the traffic culture, that is their cultural competence in traffic. The place is the relevant basis for studying a traffic culture. The purpose is therefore also to map specific places that people has found difficult. Questions answered were: how did people identify themselves? What did they want, what was wrong, who were to blame for the troubles in traffic, what should be done, and at which places did these difficulties occure? What relevance has traffic culture to effectiveness and safety in traffic? The result from this study show that traffic culture, and in turn, traffic safety is influenced by roles played by different groups in traffic. People who are cultural competent and who spend more time in the traffic room are able to manoeuvre themselves effectively in traffic and they have an important role in creating and reproducing behaviour that, in the end, constitutes a traffic culture.